Combination of Local Anesthetics and Corticosteroids as Pain Management in Supraspinatus Tendinitis: A Case Report - Nurhayati Dumbela; Alamsyah Ambo Ala Husain (HM Publisher, 2023)
Introduction: This study aimed to report the treatment of tendinitis in combination with local anesthetics and corticosteroids. Case presentation: A man, 34 years old, came to the hospital with complaints of pain in the right shoulder. This pain is felt especially when moving the right shoulder, and the patient also cannot raise his right hand. Pain when moving the right arm appeared after falling off a motorbike about 1 month ago. The intensity of pain has been getting higher for the last 14 days, especially when going to bed, so the patient complains of difficulty sleeping. The patient has been treated at the public health center for a month and has received pain relievers. Physical examination showed vital signs within normal limits and pain intensity of 8/10 based on the visual analogue scale. Examination of the extremity shows the abduction of pain starting at 60°-70° on activity and no pain on passive movement. In the special tests, the Neer test is positive, the Hawkin test is positive, and the Empty Can test is positive. The patient was diagnosed with supraspinatus tendinitis. The treatment for this patient is supraspinatus tendon injection. The anesthetic agent used was 2% lidocaine combined with 20 mg triamcinolone corticosteroids. This procedure is performed under ultrasound guidance for precise injection sites. Evaluation after the action found no side effects. After 1 month of action, the patient felt that the pain was greatly reduced (1/10) and the joint movement was not limited. Conclusion: The use of a combination of triamcinolone and lidocaine is beneficial in reducing pain in cases of supraspinatus tendinitis.